A theoretical analysis for the effect of increasing partitioning of preference structures on satisfaction with decision making. (2015) - Kira, Mohamed Ihab
The paper provides a theoretical exploration of the effect of increasing partitioning of consumers' preference structures on their satisfaction with decisions. The main finding is that the effect is an adverse one which persists, with varying magnitude, along the whole spectrum of relationships between goods, from perfect complementation to perfect substitution. The adverse effect can be offset if there is sufficient: increase in incomes, reduction in prices of goods, and/or reduction in cognitive resources targeted towards old goods. The paper concerns itself with the initial stage of consumption decision-making: the planning stage in which the groups of various goods and the average price for each group are identified and the individual divides his/her budget across the various groups. The adverse effect outlined by the paper is in synchronisation with the results of experimental research that find a similar effect for the second stage which involves the choice of a specific alternative for each good-group.